PROCESSES OF FORMATION OF ASTHETIC VIEWS IN CHRISTIANITY IN I-IV CENTURIES - GULNORA KHUDOIBERGANOVA (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Although much of the work on the study of early Christian asceticism, including several monographs, has seen the light of day in the last three decades, there has not yet been a systematic description and comprehensive analytical attempt at first-century asceticism in religious studies. The role of the religious, social, and philosophical context in its origins in ancient asceticism, as well as the existence of a coherence between the ascetic theology of the I and IV centuries, remain crucial questions in early Christian ascetic studies. In this article, we will try to address these questions by systematizing and analyzing ascetic teachings based on the texts cited in the Bible, the sacred source of Christianity.